The credit quality channel: Modeling contagion in the interbank market - Fink, Kilian; Krüger, Ulrich; Meller, Barbara; Wong, Lui-Hsian (Journal of Financial Stability, 2016)
We propose an algorithm to model contagion in the interbank market via what we term the “credit quality channel”. In existing models on contagion via interbank credit, external shocks to banks often spread to other banks only in case of a default. In contrast, shocks are transmitted also via asset devaluations and deteriorations in the credit quality in our algorithm. First, the probability of default (PD) of those banks directly affected by some shock increases. This increases the expected loss of the credit portfolios of the initially affected banks’ counterparties, thereby reducing the counterparties’ regulatory capital ratio. From a logistic regression we estimate the increase in the counterparties’ PD due to a reduced capital ratio. Their increased PDs in turn affect the counterparties’ counterparties, and so on. This coherent and flexible framework is applied to the bilateral interbank credit exposure of the entire German banking system in order to examine policy questions. For that purpose, we propose to measure the potential cost of contagion of a given shock scenario by the aggregated regulatory capital loss computed in our algorithm.